Safety council will safeguard health of patients, avert medical errors - Abd Razak, Dzulkifli (2004)
The action taken by the Ministry of Health to systematically document and manage incidences that effect patient’s safety is a laudable step on ensuring a higher standard of health care in the country. Through the establishment of a National Patient Safety Council, Malaysia are reassured that their health will be attended to more closely not only by the relevant health professionals but also by the Safety Council.